Exploring Climate Emotions in Canada’s Provincial North - Galway, Lindsay P.; Beery, Thomas (Frontiers in Psychology, 2022)
Climate change's mental and emotional dimensions are increasingly relevant as extreme events become more frequent and severe, ecosystem destruction advances, and people become increasingly aware of climate impacts and injustices. Over the last decade, research on climate emotions has rapidly advanced alongside recognizing that the climate crisis is connected to emotions in many complex ways. Specifically, there is growing evidence illustrating that climate emotions can impact health, shape climate action, and ought to be considered in climate change communication, education, and engagement efforts. This paper will explore, describe, and discuss climate emotions in the context of Canada's Provincial North: a vast region characterized by a heightened vulnerability to climate change, remoteness, political marginalization, diverse Indigenous populations, and economies and livelihoods tied to resource extraction. Empirical research on climate emotions in Canada's Provincial North and similar settings is lacking. Using postal survey data collected in two Provincial North communities (Thunder Bay, Ontario, and Prince George, British Columbia; n=627), we aim to (1) to describe climate emotions experienced in the context of Canada's Provincial North, including relationships among specific emotions; and 2) to examine if socio-demographic variables (gender, age, parenthood) show a relationship with climate emotions. Results show a high level of emotional response to climate change overall, with worry and frustration as those emotions reported by a high percentage of participants. We also find that significant difference in climate emotions between men and women. A methodological result was noted in the usefulness of the CES, which showed high reliability and high interitem correlation. The findings contribute to a greater understanding of climate emotions with particular relevance to similar settings characterized by marginalization, heightened vulnerability to climate change, urban islands within vast rural and remote landscapes, and economies and social identities tied to resource extraction. We discuss our findings in relation to the existing literature and outline key future research directions and implications.